Assessment and determination of infestation levels of phytophagous insects in a leucaena-guinea grass agro-ecosystem - Valenciaga, Nurys; Herrera, Madelen; Mora, Ciro; Noda, Aida (Cuban Journal of Agricultural Science, 2010)
A research was conducted for four years in a silvopastoral system of leucaena-guinea grass with eight years of establishment. The objective was to assess, through population monitoring, the presence and infestation of the phytophagous insects associated with the system. The sampling was stratified, with a month frequency. The phytophagous and bioregular organisms were defined and the population dynamics of the main insect-pests. Besides, the damage of the insect-pests on the tree and herbaceous strata was assessed. The data were statistically analyzed through the contingency tables and analysis of proportion comparison (chi square). Leucaena had the highest proportions of phytophagous with flying habits (91.10 %), being only the 8.90 % in guinea grass. In all seasons assessed, the tree stratum had higher proportion of organisms, highlighting as main phytophagous the psyllid H. cubana with proportions higher (P < 0.001) than 60 % in the rainy season and 80 % in the dry season. Their population indexes surpassed 10 insects/m2 in the dry season and 5 insects/m2 in the rainy season. However, no economical damage was found in the plants assessed. The Wasmannia auropunctata was the bioregulator of highest proportion (P < 0.001) in the rainy seasons of 2004 and 2005, as well as in the dry seasons of 2005, 2006 and 2007, with proportions superior to 50 %. Ants and spiders were after in proportion and lower amount, stably during both seasons. Doru taeniatum and Diomus bruneri were also collected. It is concluded that the psyllid Heteropsylla cubana remains as the main phytophagous in areas of leucaena-guinea grass, with higher incidence in the dry season, associated with sprouts or growth points of the tree legume. However, the damages by this insect were not economic due to the presence of bioregular species in these agroecosystems and their natural control. Key words: leucaena, guinea grass, insects, infestation level